CAMPUR KODE DALAM CERAMAH MAJELIS TAKLIM MASJID AS-SAKINAH PEKANBARU - ', Fatmawati; Mustafa, M Nur; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the mixed code is contained in the lecture taklim Masjid As-Sakinah Pekanbaru. This study aimed to describe code-mixing in the form of words, phrases, clauses, and the driving factors behind code-mixing in taklim Masjid As-Sakinah Pekanbaru. Helpful research theoretically and practically. This study is a qualitative research and descriptive method. Techniques used in data collection in this study is a technique to record and log techniques. The data have been collected and analyzed by several stages of data inventory, classify the data, describing data, and summarize the results of research. This research data is sourced from a document recording delivered peceramah taklim Masjid As-Sakinah Pekanbaru. From the research that has been done, the researchers found 215 data. Data that is 153 words, 41 Data phrase, and 21 klausa.Jadi the data, the data most is the word .. Based on the results of this study concluded that the language used in the code-mixing speaker when bercemarah is Indonesian and Minang. Speakers use the language because of the audience more Minang Minangkabau ethnic group, so that the audience will more easily understand the lectures delivered. In the lecture, speakers should pay attention to code-mixing spoken to avoid the occurrence of misunderstanding on the listener.Key Words: Mixed Code, Lectures, Pekanbaru